Screening and Identification of Chitinase-Producing Trichoderma species - Ubolsuk, Chosita; Pornsuriya, Chaninun (Princess of Naradhiwas University Journal, 2021)
Most of the antagonistic Trichoderma species produce chitinase against plant pathogenic fungi which is one of the antagonistic properties. Therefore, the aim of this research was to determine chitinase production of Trichoderma species and to identify the highest chitinase-producing isolate at the species level. Twenty-six isolates of Trichoderma species were primary tested for chitinase production on chitinase detection medium at pH 4.7. Chitinase activity was determined using DNS method by detection of reducing sugar in PDB culture filtrates. The results showed that 22 isolates of Trichoderma species produced chitinase and the isolate T-GL7 showed the highest chitinase activity of 0.0082 U/ml. Confirmation by morphological characteristic and nucleotide sequence of the internal transcribed spacer (ITS) showed that the T-GL7 was T. reesei.